Pollution of Seti River in Pokhara: An Anthropological Perspective - Bhandari, Amrit Kumar (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Seti River is one of important components of the ecology of Pokhara so it holds a great significance for maintaining ecological balance and fulfilling different types of needs of people here. But only a few people are aware of its real value while others are pretending to be unaware of this and are accelerating its pollution. It's true that its pollution is not as devastating as the pollution of the Bagmati and the Vishnumati in Kathmandu. But its pollution is increasing, if it goes on increasing like this, it will surely reach that devastating stage in the near future which will threaten the existence of eco-system and components including human kind inhabiting around its vicinity. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1493 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.11-33